Differences in Dysmenorrhea Levels among Female Adolescent Users of Conventional and Electronic Cigarettes - Pertiwi, Vynna Leyra; Lindayanti, Emi; Nurhidayah, Ida (Inspirasi Foundation, 2026)
Introduction: Dysmenorrhea is a common reproductive health problem among adolescent females and is often associated with various lifestyle factors, including smoking behavior. The increasing use of conventional cigarettes and electronic cigarettes among young women raises concerns regarding their potential impact on menstrual pain. Objective: This study aimed to compare the level of dysmenorrhea between adolescent females who use conventional cigarettes and those who use electronic cigarettes. Method: This research employed a quantitative approach with a cross-sectional design and involved 70 respondents aged 15–24 years in Sumedang Regency, consisting of 35 conventional cigarette users and 35 electronic cigarette users. Data were collected using an online and offline questionnaire that included demographic characteristics, smoking behavior adapted from the Global Youth Tobacco Survey (GYTS), and menstrual pain measured using the Numeric Rating Scale (NRS). The data were analyzed using the Mann–Whitney test with a significance level of 0.05. Result: The results showed that most respondents in both groups experienced severe dysmenorrhea, with mean pain scores of 7.114 for conventional cigarette users and 7.200 for electronic cigarette users. Statistical analysis indicated no significant difference between the two groups (p = 0.833). Conclusion: These findings suggest that both types of smoking may have similar biological impacts on menstrual pain due to the presence of nicotine. Further studies are recommended to assess additional confounding factors and measure nicotine exposure more precisely.